2018
DOI: 10.1590/0001-3765201820160870
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Lamiaceae plant extracts in clinical isolates of multidrug-resistant bacteria

Abstract: The antibacterial activity of plant extracts of the Lamiaceae family was evaluated against clinical isolates of multi-resistant Gram-negative bacteria by broth microdilution technique. Promising results were obtained considering that all extracts were active for at least two bacterial species with MIC ranging from 0.5 to 2.0 mg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
(15 reference statements)
3
12
0
Order By: Relevance
“…Regarding the activity of extract against multidrugresistant strains, Assis et al (2018) evaluated the ethanol extract of three Lamiaceae species against Acinetobacter baumannii, Klebsiella pneumoniae, Escherichia coli and Pseudomonas aeruginosa clinical isolates with multidrugresistant profile. They identified that the P. barbatus extract was the most effectiveness, exhibiting MIC of 2000, 1000, 1000 and 500 µg.mL -1 respectively, however, they did not identify the extract composition.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the activity of extract against multidrugresistant strains, Assis et al (2018) evaluated the ethanol extract of three Lamiaceae species against Acinetobacter baumannii, Klebsiella pneumoniae, Escherichia coli and Pseudomonas aeruginosa clinical isolates with multidrugresistant profile. They identified that the P. barbatus extract was the most effectiveness, exhibiting MIC of 2000, 1000, 1000 and 500 µg.mL -1 respectively, however, they did not identify the extract composition.…”
Section: Discussionmentioning
confidence: 99%
“…28 Many of these diseases are caused by bacterial infections and numerous studies have reported antibacterial properties for species of this genus. [41][42][43] However, many of these studies either do not quantify the activity, or report low to moderate activity for the extracts and oils of these plants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted with plant extracts and essential oils have demonstrated efficacy of some compounds with antimicrobial activities against bacteria [29][30][31] and fungi. [32][33][34] These compounds are secondary metabolites of plants with variations in their structure and chemical composition resulting in different antimicrobial effects.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, others considered MIC values ≤ 1 mg/ml as satisfactory and promising. 43,30 Considering this parameter, the inhibitory effects results obtained with crude extracts from P. cattleianum, R. officinalis and O. vulgare were characterized as satisfactory against S. aureus. However, none of the plant extracts showed satisfactory results against A. parasiticus, according to the recommendations of other studies.…”
Section: Discussionmentioning
confidence: 99%